EFEITOS PROTETORES E ERRADICANTES DE FUNGICIDAS NO CONTROLE DE ANTRACNOSE NA CULTURA DA SOJA - Cavalcanti, Vittor; Sganzerla, Felipe; Souza, Eli Domingo; Romero, Rogério; Blanco, Neder; Nascimento, Sergio (ANAIS DO ENIC, 2018)
-